India's potential economic growth: measurement issues and policy implications - Ranjan, Rajiv; Dhal, Sarat C.; Jain, Rajeev (2007)
This paper provides estimates of the potential growth rate for India by adopting alternative approaches of statistical trend filtering techniques and a production function. The Hodrick-Prescott filtering technique leads to estimated potential GDP growth of about 7 per cent. The warranted growth rate hovers around 8 per cent for the more recent period. The multivariate production function framework yields a potential growth of 6.6 per cent, which could be an underestimate given the data limitations. From the policy perspective, changes in policy instruments are linked to measures of output and the inflation gap within the framework of a policy reaction function. Empirical results showed that policy actions have significant association with output gap and inflation gap. - Reproduced.
Keywords: Economic growth